Detection of Cyclospora cayetanensis by PCR in Wasit Province, Iraq - Abdulsada A. Rahi; Israa N. Abed Al-Saadi; Yoosra N. Abed Al-Saadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present study aimed to detect the Cyclospora cayetanensis among patients that attended in Al-karamaTeaching Hospital and General Hospital of Martyr Fairuz in Wasit City. The sample were collected fromOctober 2015 to April 2016. Thirty stool samples were collected from patients that suffering from diarrhea,their aged between 1 year to 50 years old from both genders who attended the hospitals at Wasit province.Data was collected using a questionnaire form including information about gender, age, location. Stoolsamples were examined by PCR technique to detect the presence of Cyclospora cayetanensis. The resultshowed that 8 of 30 (26.7%) samples were positive while 22 of 30 (73.3%) were negative. Our study isconsidered as a first study that detect the Cyclospora cayetanensis in Wasit province, Iraq. This study wasaimed to determine the prevalence of C. cayetanensis in Wasit Province, Iraq.